PEMBERDAYAAN MASYARAKAT TENTANG DIGITAL MARKETING DAN DIGITAL PAYMENT KEPADA USAHA MIKRO KECIL DAN MENENGAH (UMKM) - Gita Octaviani; Anisa Putri; Diana Fajarwati (An-Nizam, 2022)
The Covid-19 pandemic has shaken the entire world economy, including Indonesia. During the 1998 financial crisis in Indonesia, micro, small and medium enterprises (MSMEs) were able to survive and support the economy. Digital marketing and digital payments are one of the renewals of today's technological advances. The existence of a breakthrough like this forces MSME actors to transform into the digital era. At the time of the COVID-19 pandemic that had hit Indonesia, and the government's policies that limited the mobility of the community, digital marketing and digital payments were the right solution for MSME players to stay afloat and help improve the Indonesian economy. Based on the results of activities in the Bekasi Jati village about digitizing marketing and digitizing payments for MSME actors by conducting registration training to shopee application platform in the area, there are still many things that need to be improved, starting from having a bank account and replacing their mobile phones that support them to market their products on the internet. E-commerce in order to make their business advanced in technology-based business competition. The impact of the program that the author has given to MSME actors who have registered in e-commerce is very helpful for them in terms of product marketing and increasing their income during the covid-19 pandemic that is hitting the surrounding environment.